All Days 2009
DOI: 10.2118/119884-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Automation: Technologies, Terminology and Parallels With Other Industries

Abstract: Drilling Automation is a rapidly developing area of technology that is seeing growing interest within the drilling community. The SPE set up a new Technical Section devoted to the subject as it relates to downhole performance, and the IADC has created a committee with a focus on surface processes. As with any emerging technology, the associated jargon is evolving rapidly, and different terms are used by different groups to refer to similar concepts with the potential for confusion and misunde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The higher data rates can support more-sophisticated services such as detailed borehole imaging, high-frequency drillstring dynamics, and proactive control of drilling using rotary closed-loop systems. Drilling automation is an area of growing interest, with SPE having recently established a technical section on the subject and the International Association of Drilling Contractors an Advanced Rig Technology Committee (Thorogood et al 2009). …”
Section: Organizational-and Behavioral-change Managementmentioning
confidence: 99%
“…The higher data rates can support more-sophisticated services such as detailed borehole imaging, high-frequency drillstring dynamics, and proactive control of drilling using rotary closed-loop systems. Drilling automation is an area of growing interest, with SPE having recently established a technical section on the subject and the International Association of Drilling Contractors an Advanced Rig Technology Committee (Thorogood et al 2009). …”
Section: Organizational-and Behavioral-change Managementmentioning
confidence: 99%
“…In consideration of the complexity of the wellbore stability workflow and the challenges associated with its automation, different levels of automation may be targeted, as suggested by Thorogood et al (2010). These levels distinguish between low automation stages, where the user maintains control, and fully autonomous systems that do not require any user interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Such tools would provide reliable integration of MPD-related activities, allowing humans to concentrate on higher-level decisions, while leaving the reliable execution of lower-level decisions to automation. MPD automation has been limited in the field to date (Santos et al 2007;Fredericks et al 2008;Bjørkevoll et al 2008;Godhavn 2009), but its potential is growing (Thorogood et al 2009). Automation has proved its reliability, safety, and ability to outperform humans in oil refining (Saputelli et al 2005(Saputelli et al , 2006Nikolaou 2008) and has shown its potential in traffic management (Godhavn et al 1996) and aerospace control (Maciejowski and Jones 2003).…”
Section: Introductionmentioning
confidence: 99%